MERUMUSKAN TUJUAN JANGKA PENDEK - Sahat M.P. Tanjung (Jurnal Manajemen Kewirausahaan, 2017)
Thus in wide-explained numbers of wording the formulation of Long-Term Planning as one of the very important milestones in Strategy Formulation we can read in some books and publications. But it is to be a great wonder that the formulation of Short-Term Planning never explained in all publications. Notwithstandingly we know that the formulation of Short-Term Planning is yet another very important milestones.It is impossible to have the enshaped Long-Term Planning to be realized without a neat formulation of the Short-Term Planning. Those long-termed shape will only be an empty dream.So far by practices the formulation of Short-Term Planning is done by improvisation headed by key-personnel. Such as implementing the plan as the one that has ever be implemented, or by gradual timely planning and evaluation, or by Expert opinions. These could endanger the Long-Term Planning due to the actual change and the grip of actual conditions may occur anytime in the progres.Thus by this journal two sets of formulation suggested to be proposed, avoiding the dangers may come by improvisation. Namely the usage of Barchart and the usage of Network Planning. Keywords:        Formulation, Long-Term Planning, Short-Term Planning, Strategy Formulation, Barchart, Network Planning.